Construction of an efficient Claviceps paspali cell factory for lysergic acid production - Hu, Mingzhe; Zhou, Yu; Du, Siyu; Zhang, Xuan; Tang, Shen; Yang, Yong; Zhang, Wei; Chen, Shaoxin; Huang, Xuenian; Lu, Xuefeng (Frontiers in Bioengineering and Biotechnology, 2023)
Lysergic acid (LA) is the key precursor of ergot alkaloids, and its derivatives have been used extensively for the treatment of neurological disorders. However, the poor fermentation efficiency limited its industrial application. At the same time, the hardship of genetic manipulation has hindered the metabolic engineering of Claviceps strains to improve the LA titer further. In this study, an efficient genetic manipulation system based on the protoplast-mediated transformation was established in the industrial strain Claviceps paspali. On this basis, the gene lpsB located in the ergot alkaloids biosynthetic gene cluster was deleted to construct the LA-producing cell factory. Plackett-Burman and Box-Behnken designs were used in shaking flasks, achieving an optimal fermentation medium composition. The final titer of LA and iso-lysergic acid (ILA) reached 3.7 g·L-1, which was 4.6 times higher than that in the initial medium. Our work provides an efficient strategy for the biosynthesis of LA and ILA and lays the groundwork for its industrial production.